Association of Helicobacter pylori Infection With Colon Cancer and Adenomatous Polyps - Fatemeh Teimoorian; Mohammad Ranaei; Karimollah Hajian-Tilaki; Javad Shokri Shirvani; Zeinab Vosough (Iranian Society of Pathology, 2018)
Background and objective: Helicobacter pylori infection is one of the most common chronic bacterial infections in the world, especially in the developing countries. This bacterium is the cause of many diseases such as lymphoma, gastritis, peptic ulcers, and stomach cancer. According to recent reports, H. pylori infection can potentially increase the risk of colon cancer. The current study aimed at investigating the association of H. pylori infection and the risk of colorectal cancer and adenomatous polyps.Methods: The current study was conducted on 50 patients with colon cancer and adenomatous polyps as the case group and 100 subjects with no specific pathologies (i e, polyps, neoplasms, or inflammatory diseases) as the control group. Blood samples were collected from the patients in order to assess the presence of anti-Helicobacter pylori infection antibodies, and the serum titer levels of anti-Helicobacter pylori IgG and IgA antibodies were measured using indirect enzyme-linked immunosorbent assay (ELISA) and a kit procured by Pishtaz Teb Company (Iran).Results: A total of 33 patients in the current study had adenomatous polyps and 17 had colon cancer. H. pylori infection (IgA >20 U/mL and IgG >10 U/mL) was significantly more prevalent in the patients with colon cancer and adenomatous polyps compared with the healthy controls (P= 0.003, P= 0.039, respectively). Conclusion: The obtained results suggested that H. pylori infection can be considered as a risk factor for colon cancer and adenomatous polyps.